2021
DOI: 10.1186/s13041-021-00771-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in vitro model for analyzing mitochondrial ultrastructure in PRKN-mutated patient iPSC-derived dopaminergic neurons

Abstract: Mitochondrial structural changes are associated with the regulation of mitochondrial function, apoptosis, and neurodegenerative diseases. PRKN is known to be involved with various mechanisms of mitochondrial quality control including mitochondrial structural changes. Parkinson’s disease (PD) with PRKN mutations is characterized by the preferential degeneration of dopaminergic neurons in the substantia nigra pars compacta, which has been suggested to result from the accumulation of damaged mitochondria. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Conversely, Parkin patient-derived NPCs showed a subtle, but significant elevation in mitochondrial fragmentation that dose-dependently increased in severity with copper exposure, a known environmental risk factor for PD [ 100 ]. A recent study using Parkin KO iPSC-derived neurons elegantly showed that smaller and less functional mitochondria were present in dopaminergic, but absent in non-dopaminergic neurons using a tyrosine hydroxylase reporter cassette and correlative light electron microscopy [ 101 ]. This suggests that dopaminergic neurons possess intrinsic physiological differences, making them particularly vulnerable compared to other types of neurons.…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
“…Conversely, Parkin patient-derived NPCs showed a subtle, but significant elevation in mitochondrial fragmentation that dose-dependently increased in severity with copper exposure, a known environmental risk factor for PD [ 100 ]. A recent study using Parkin KO iPSC-derived neurons elegantly showed that smaller and less functional mitochondria were present in dopaminergic, but absent in non-dopaminergic neurons using a tyrosine hydroxylase reporter cassette and correlative light electron microscopy [ 101 ]. This suggests that dopaminergic neurons possess intrinsic physiological differences, making them particularly vulnerable compared to other types of neurons.…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
“…The PRKN gene encodes the Parkin RBR E3 ubiquitin protein ligase, a protein involved in the pathway of protein ubiquitination. In particular it has been studied in the mitochondrial mechanisms of quality control and associated with the regulation of mitochondrial apoptosis and neurodegenerative diseases [ 31 ]. PRKN mutations are known to be involved with early onset familial and autosomal recessive juvenile Parkinson’s disease [ 32 , 33 ], likely due to the preferential degeneration of dopaminergic neurons in the substantia nigra pars compacta, resulting from the accumulation of damaged mitochondria [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular it has been studied in the mitochondrial mechanisms of quality control and associated with the regulation of mitochondrial apoptosis and neurodegenerative diseases [ 31 ]. PRKN mutations are known to be involved with early onset familial and autosomal recessive juvenile Parkinson’s disease [ 32 , 33 ], likely due to the preferential degeneration of dopaminergic neurons in the substantia nigra pars compacta, resulting from the accumulation of damaged mitochondria [ 31 ]. Interestingly, dopamine plays a central role in the Reward system, which regulates the effects of decision-making and induces approach behavior.…”
Section: Discussionmentioning
confidence: 99%
“…iPSC-derived mutant PARK2 neurons exhibited increased oxidative stress and aberrant activation of the NRF2 pathway with impaired mitochondrial function and α-synuclein accumulation [106]. Similarly, iPSC-derived mutant PARK2 dopaminergic neurons, carrying a GFP expression cassette at the TH locus, showed small and less functional neurons with a decline in mitochondrial membrane potential, suggesting a mitochondria-dependent mechanism involved in dopaminergic neuron susceptibility to PD [107]. A potential link between α-synuclein and impairments in mitochondrial dynamics and bioenergetics is suggested by the direct interaction with the OXPHOS components as demonstrated in proteomic studies [108,109].…”
Section: Neurodegenerationmentioning
confidence: 98%